Dry-sprinkled terrazzo flooring material, method of manufacture and method of construction
Patent Information
- Application Number
- CN202610643674.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-11
- Publication Date
- 2026-10-27
AI Technical Summary
其三,传统施工工艺依赖混凝土自然硬化,早期强度低,施工周期长,且容易因施工时机掌握不当而导致颜色不均
[0021]本发明针对传统干撒地坪只有单一的耐磨层,与基层混凝土界面清晰,易分层脱落等问题,开发具有结合力强、耐磨性好、装饰性高、施工周期短等优点的干撒磨石地坪材料,其具有以下的技术特点和有益效果。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of building materials technology, specifically relating to a dry-spread terrazzo flooring material, its preparation method, and its construction method. Background Technology
[0002] In the field of architectural decoration, marble and ceramic tiles are currently the most common flooring materials. However, public spaces such as schools, shopping malls, and entertainment venues have placed higher demands on the decorative effects of flooring, while also creating a continuous demand for novel and diverse decorative styles. Against this backdrop, terrazzo flooring has gradually gained market attention.
[0003] Terrazzo flooring initially appeared in the form of inorganic terrazzo. Inorganic terrazzo refers to flooring systems made by binding aggregates with inorganic cementitious materials such as cement and glass, such as traditional cement-based terrazzo and glass-based terrazzo. This type of flooring has good fire resistance and a unique aesthetic appeal. Among them, terrazzo is a relatively common type of inorganic terrazzo, but it is prone to quality problems such as hollow areas, insufficient plasticity, brittleness, and cracking due to the limitations of cement materials.
[0004] With the development of organic materials, terrazzo flooring using organic polymers as binders has emerged, also known as organic terrazzo. Among them, epoxy terrazzo is currently the most widely used type.
[0005] On the other hand, in the field of wear-resistant flooring, the "dry-spreading method" is a mature construction technique. The typical procedure involves dry-spreading wear-resistant aggregates such as corundum onto the surface of the concrete base layer before or after initial setting, followed by smoothing, leveling, finishing, and curing. The aggregates used are primarily corundum, quartz sand, and metallic aggregates, with the main goal of achieving excellent surface wear resistance. However, this technology has the following prominent problems: Firstly, ordinary dry-spread emery flooring has a monotonous appearance and poor decorative properties; Secondly, existing dry-spread terrazzo flooring using decorative aggregates has insufficient bonding strength between the aggregates and the concrete base layer, which easily leads to aggregate detachment and surface sanding. Third, traditional construction techniques rely on the natural hardening of concrete, resulting in low early strength, long construction cycles, and uneven coloring due to improper timing of construction.
[0006] In addition, in existing epoxy terrazzo and other flooring systems, the aggregate and cementitious materials are usually only physically coated and interlocked, with weak chemical bonding, which also leads to problems such as cracking; at the same time, the aggregate gradation is often relatively simple, resulting in insufficient system density. Summary of the Invention
[0007] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a dry-spread terrazzo flooring material, a preparation method and a construction method thereof. The dry-spread terrazzo flooring material has the advantages of strong bonding force, good wear resistance, high decorative effect and short construction period.
[0008] To solve the above problems, the present invention is achieved through the following technical solution: The first objective of this invention is: A dry-spread terrazzo flooring material is provided, which comprises the following raw material components in parts by weight: 30-50 parts of cementitious material, 1-5 parts of composite admixture, 40-70 parts of dry-spreading inorganic-organic composite surface-activated modified gradient aggregate, 0.1-3 parts of water-reducing agent, and 0.1-2 parts of cellulose ether; The cementitious material includes: A mixture composed of rapid-hardening sulfoaluminate cement and ordinary silicate cement in a mass ratio of 1-3:7-9; this composite system utilizes the early strength characteristics of sulfoaluminate cement and the later-stage stability of silicate cement, enabling the material to quickly reach grindable strength while ensuring long-term performance. The composite admixture includes: A mixture composed of citric acid retarder, lithium carbonate early strength agent, and organosilicon defoamer in a mass ratio of 0.1–1:0.1–2:0.1–0.5; This composite admixture coordinates and controls the hydration rate, ensuring sufficient working time for application, while promoting early strength development, eliminating air bubbles, and improving density. The dry-spreading-specific inorganic-organic composite surface-activated modified gradient aggregate includes: Coarse aggregate, medium aggregate, fine aggregate and micro filler are subjected to surface double modification treatment and graded in a mass ratio of 2-4:1-3:1-2:0.5-1. The surface dual modification treatment is as follows: first, the aggregate is hydrophobically modified with vinyltriethoxysilane, and then grafted with polycarboxylate superplasticizer, so that the aggregate surface has both chemical reactivity and dispersibility with cement hydration products. This treatment makes the aggregate surface both hydrophobic and chemically reactive and dispersible with cement hydration products, significantly enhancing the interfacial bonding between the aggregate and the cement paste. The dry-spread terrazzo flooring material is applied and used in the following ways: After the concrete base layer is pre-activated at the interface, the dry-spread terrazzo flooring material is spread in two stages, first vertically and then horizontally, and then compacted using a vibratory roller.
[0009] The initial setting time of the prepared flooring material is 45-60 minutes, the final setting time is 2-3 hours, and the 24-hour compressive strength is ≥30MPa.
[0010] A further optimization of the dry-spread terrazzo flooring material of the present invention is as follows: The coarse aggregate is sintered ceramic particles or dyed basalt with a particle size of 2-4 mm. The medium aggregate is natural quartz sand with a particle size of 0.5 to 1.5 mm; The fine aggregate is nano-alumina modified glass microspheres with a particle size of 0.1-0.3 mm; The microfiller is a mixture of activated metakaolin with a particle size of 20-100 nm and nano-calcium carbonate in a mass ratio of 1-2:0.5-1.
[0011] The second objective of this invention is: A method for preparing the aforementioned dry-spread terrazzo flooring material is provided, comprising the following preparation steps: According to the formula, the gelling material, composite additive, water-reducing agent and cellulose ether are added to the dry powder mixing equipment and mixed evenly. Then, the dry-spreading special inorganic-organic composite surface-activated modified gradient aggregate is added, and the stirring speed is increased to continue mixing for 10 to 20 minutes to ensure that all components are fully dispersed and mixed evenly to obtain the dry-spreading terrazzo flooring material.
[0012] The third objective of this invention is: A method for constructing the aforementioned dry-spread terrazzo flooring material is provided, comprising the following steps: S1. Concrete base pretreatment: Pour concrete base and level it; S2. Interface pre-activation: Spray nano-silica sol interface agent onto the leveled concrete base surface; S3. First application: When the concrete surface reaches the predetermined state, the dry-spread terrazzo flooring material is evenly spread perpendicular to the concrete pouring direction; S4. First compaction: Use a vibratory roller to compact the surface of the spread dry-spread terrazzo flooring material; S5. Second application: Evenly spread the dry-spread terrazzo flooring material parallel to the concrete pouring direction; S6. Second compaction: Use a vibratory roller to compact the surface of the spread dry-spread terrazzo flooring material and smooth the edges and corners; S7. Maintenance and Polishing: After the construction is completed, moisturize and maintain the surface, then polish and grind. in, The dry-spread terrazzo flooring material used in the first spreading step S3 and the second spreading step S5 is the same material with the same proportion; or, The dry-spread terrazzo flooring materials used in the first spreading in step S3 and the second spreading in step S5 are two different materials with different proportions, and the weight ratio of coarse aggregate in the material used in the first spreading is higher than that in the material used in the second spreading. Regardless of the method described above, under vibratory compaction, coarse aggregate preferentially sinks and embeds into the base layer, while medium and fine aggregates and micro-fillers fill the upper layer, thus naturally forming a gradient distribution of aggregates in the vertical direction. Using two different proportions of materials provides flexible construction options to meet diverse decorative designs (such as emphasizing the exposed coarse aggregate effect or pursuing a more delicate surface texture).
[0013] The construction method of the dry-spread terrazzo flooring material described in this invention is further optimized as follows: The vibration frequency of the vibratory roller in each compaction is 30-50 Hz, and the number of compaction passes is 2-4.
[0014] The construction method of the dry-spread terrazzo flooring material described in this invention is further optimized as follows: In step S2, the spraying dosage of the nano-silica sol interface agent is 0.1-0.2 kg / m², which activates the surface activity of concrete.
[0015] The construction method of the dry-spread terrazzo flooring material described in this invention is further optimized as follows: In step S3, the predetermined state is when the water seepage on the concrete surface disappears and the depth of finger pressing is 3-5 mm (1-2 hours earlier than the traditional dry spreading time).
[0016] The construction method of the dry-spread terrazzo flooring material described in this invention is further optimized as follows: In step S3, the amount of dry-spread terrazzo flooring material used in the first application is 6-8 kg / m². And / or, In step S5, the amount of dry-spread terrazzo flooring material used in the second spreading is 4-6 kg / m².
[0017] The construction method of the dry-spread terrazzo flooring material described in this invention is further optimized as follows: The compaction described in step S4 causes the coarse aggregate in the dry-spread terrazzo flooring material to embed into the concrete base layer to a depth of 2-3 mm.
[0018] The construction method of the dry-spread terrazzo flooring material described in this invention is further optimized as follows: The floor structure formed by the construction method is a gradient structure integrated with the concrete base layer, comprising, from bottom to top: The surface consists of a penetrating bonding layer (CSH gel layer) formed by the reaction of nano-silica sol with hydration products on the concrete surface; an aggregate embedding layer formed mainly by the mechanical interlocking and chemical bonding of coarse aggregate in dry-spread terrazzo flooring material with cement hydration products; and a dense surface layer formed mainly by medium aggregate, fine aggregate and micro filler in dry-spread terrazzo flooring material.
[0019] The construction method of the dry-spread terrazzo flooring material described in this invention is further optimized as follows: The thickness of the permeation bonding layer is 1-2 mm; The thickness of the aggregate embedding layer is 3-4 mm; The thickness of the dense surface layer is 1 to 2 mm.
[0020] Through the synergistic effect of the aforementioned materials and construction methods, the resulting flooring possesses a unique three-layer integrated structure of "gradient penetration-density". This structure, with a total thickness of 5-8mm, is seamlessly integrated with the base concrete, without a clear interface, fundamentally solving the problem of delamination and detachment.
[0021] This invention addresses the problems of traditional dry-spread terrazzo flooring, which has only a single wear-resistant layer, a clear interface with the base concrete, and is prone to delamination and detachment. It develops a dry-spread terrazzo flooring material with advantages such as strong adhesion, good wear resistance, high decorative properties, and short construction period. It has the following technical features and beneficial effects.
[0022] (1) By using surface double modification technology, the aggregate is endowed with excellent interfacial affinity and dispersibility, so that it forms chemical bonds and mechanical interlocking with cement hydration products, and the bonding strength is greatly improved.
[0023] (2) The aggregate system with multi-scale (in the preferred scheme, it reaches the millimeter to nanometer scale) gradient gradation achieves the densest packing, forming a highly dense and high-strength mortar, which significantly improves wear resistance and compressive strength.
[0024] (3) The sulfoaluminate-silicate composite cementitious system, combined with special composite admixtures, achieves precise control of setting time and rapid improvement of early strength (24-hour compressive strength ≥30MPa), which greatly shortens the construction cycle.
[0025] (4) The “interface pre-activation-layer directional spreading-vibration compaction” process ensures the effective embedding of aggregates at different levels and the formation of structural gradients, ultimately resulting in a highly durable floor integrated with the base layer.
[0026] (5) The product not only has Class A fireproof and low VOC environmental protection characteristics, but also achieves rich decorative effects through exposed colored aggregates, overcoming the shortcomings of poor decoration of traditional dry-spread flooring. Detailed Implementation
[0027] To make the objectives, technical solutions, and advantages of this invention clearer, the invention is described in detail below with reference to specific embodiments. It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the invention. Any simple improvements to the preparation method of this invention based on the inventive concept are within the scope of protection of this invention.
[0028] Example 1: A dry-spread terrazzo flooring material and its preparation method (specific raw materials and dosages are shown in Table 1). The dry-spread terrazzo flooring material comprises the following raw material components in parts by weight: 30-50 parts of cementitious material, 1-5 parts of composite admixture, 40-70 parts of dry-spreading inorganic-organic composite surface-activated modified gradient aggregate, 0.1-3 parts of water-reducing agent, and 0.1-2 parts of cellulose ether; The cementitious material includes: A mixture composed of rapid-hardening sulfoaluminate cement and ordinary silicate cement in a mass ratio of 1-3:7-9; The composite admixture includes: A mixture composed of citric acid retarder, lithium carbonate early strength agent, and organosilicon defoamer in a mass ratio of 0.1–1:0.1–2:0.1–0.5; The dry-spreading-specific inorganic-organic composite surface-activated modified gradient aggregate includes: Coarse aggregate, medium aggregate, fine aggregate and micro filler are subjected to surface double modification treatment and graded in a mass ratio of 2-4:1-3:1-2:0.5-1. The surface dual modification treatment is as follows: first, the aggregate is hydrophobically modified with vinyltriethoxysilane, and then grafted with polycarboxylate superplasticizer, so that the aggregate surface has both chemical reactivity and dispersibility with cement hydration products. The dry-spread terrazzo flooring material is prepared by the following method: According to the formula, the gelling material, composite additive, water-reducing agent and cellulose ether are added to the dry powder mixing equipment and mixed evenly. Then, the dry-spreading special inorganic-organic composite surface-activated modified gradient aggregate is added, and the stirring speed is increased to continue mixing for 10 to 20 minutes to ensure that all components are fully dispersed and mixed evenly to obtain the dry-spreading terrazzo flooring material.
[0029] The dry-spread terrazzo flooring material is applied and used in the following ways: After the concrete base layer is pre-activated at the interface, the dry-spread terrazzo flooring material is spread twice, first vertically and then horizontally (the two applications use the same material ratio), and then compacted using a vibratory roller (see the corresponding content in the instruction manual for details). Example 2
[0030] Example 2 is prepared in the same way as Example 1, the main difference being that the amount of each raw material component is different. Example 3
[0031] Example 3 was prepared using the same method as Example 1, the main difference being that Example 3 used a specific modified gradient aggregate: The coarse aggregate is sintered ceramic particles with a particle size of 2-4 mm; The medium aggregate is natural quartz sand with a particle size of 0.5 to 1.5 mm; The fine aggregate is nano-alumina modified glass microspheres with a particle size of 0.1-0.3 mm; The microfiller is a mixture of activated metakaolin with a particle size of 20-100 nm and nano-calcium carbonate in a mass ratio of 1-2:0.5-1.
[0032] Comparative Example 1 is a traditional dry-spread emery floor.
[0033] Comparative Example 2 is basically the same as Example 1 in terms of composition and preparation method. The main difference is that Comparative Example 2 uses ordinary gradient aggregate and does not perform the surface double modification treatment of the aggregate as in Example 1.
[0034] Comparative Example 3 and Example 1 have the same raw material composition and dosage. The main difference is that Comparative Example 3 uses the traditional spreading and polishing process, instead of the specific process of Example 1.
[0035] Table 1. Raw material composition (parts by weight) of flooring materials in the examples and comparative examples
[0036] Performance Testing and Results Analysis For the flooring materials prepared in Examples 1-3 and Comparative Examples 1-2, sample construction was carried out according to the same construction process (Examples 1-3 and Comparative Example 2 adopted the construction method described in this invention, while Comparative Example 1 adopted the traditional construction method in its product manual). The performance of the formed sample flooring was tested according to relevant national or industry standards. The test results are shown in Table 2.
[0037] Table 2. Floor performance test results of the examples and comparative examples
[0038] Examples 1 and 2 demonstrate comprehensive and significantly superior performance compared to the closest comparative example 2. In particular, the bond strength is increased by over 80% (reaching over 2.6 MPa), and the 24-hour compressive strength exceeds 30 MPa. This indicates that the synergistic effect of the "dual surface modification," "rapid-hardening cementitious system," and "specific construction method" employed in this invention has brought about outstanding and substantial results—fundamentally solving the industry problems of decorative finish and slow construction.
[0039] Although the proportions of Example 1 and Example 2 are different, their performance is excellent and at the same high level, which proves the rationality of the proportion range and the stability of the effect of the present invention.
[0040] Example 3 used a specific high-performance aggregate with preferred selection criteria. It achieved the best values among all samples in key indicators such as 28-day compressive strength. This demonstrates that further selection of specific high-performance aggregates (such as sintered ceramic particles and nano-modified glass microspheres) can produce further beneficial technical effects, namely, obtaining a floor with stronger bonding, greater wear resistance, and longer decorative durability.
[0041] Compared to Comparative Example 1 (traditional corundum flooring), the present invention (Examples 1-3) has overwhelming advantages in 24-hour strength, final strength, and construction efficiency, and endows the flooring with superior decorative properties (a qualitative leap from 0 to 1). Although some indicators of pure physical wear resistance are similar in Comparative Example 1, the present invention opens up a new direction of "integrated decoration and wear resistance," providing a brand-new product with better overall performance and meeting modern aesthetic needs.
[0042] Traditionally, it is believed that decorative properties, high strength, and high durability are difficult to achieve simultaneously in dry-sprinkled flooring. This invention successfully breaks this technical prejudice through an innovative material interface chemistry method.
[0043] The comparison between Comparative Example 3 and Example 1 shows that although both use the same base materials, the bond strength and surface density (observed from cross-sectional structure) of Comparative Example 3 are significantly lower than those of Example 1, and the time required to make the surface walkable is longer. This indicates that even with the modified aggregate of this invention, without employing the specific construction process of "interface pre-activation - layered directional spreading - vibratory compaction," it is still impossible to obtain an optimal, gradient-integrated high-performance floor structure. This process is a necessary means to ensure that the performance of the modified aggregate is fully utilized and ultimately forms an integrated structure of "penetrating bonding layer - aggregate embedding layer - surface dense layer."
[0044] Furthermore, this technical solution also conducted comparative tests on two different proportions of dry-spread terrazzo flooring materials used during construction. In the first spreading application, the proportion of coarse aggregate was higher, with a mass ratio of coarse aggregate, medium aggregate, fine aggregate, and microfiller of 4:1:1:0.5. In the second spreading application, the proportion of medium and fine aggregate was higher, with a mass ratio of 1:3:2:1. The remaining raw material composition and preparation methods of both materials were the same as in Example 1. The construction steps, parameters, and curing and grinding were the same as in Example 1. Empirical tests showed that the resulting flooring performance was comparable to the data in Example 1 in Table 2, and the embedding effect of the coarse aggregate was more significant.
[0045] In summary, this invention, through the synergistic effect of specific material formulations (especially surface double modification and gradient gradation of aggregates) and specific construction methods (interface pre-activation, layered directional spreading, and vibration compaction), successfully prepares a flooring system that combines excellent decorative effect, ultra-high strength, outstanding wear resistance and anti-slip performance, and rapid construction.
[0046] In summary, the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any changes, modifications, and evolutions made by those skilled in the art without departing from the scope of the present invention based on the disclosed technical content shall be considered equivalent embodiments of the present invention. Furthermore, any changes, modifications, and evolutions made to the above embodiments based on the essential technology of the present invention shall still fall within the protection scope of the present invention.
[0047] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0048] Experimental methods not specified in this invention are generally performed under conventional conditions or as recommended by the manufacturer.
[0049] Unless otherwise stated, the various optimized technical solutions in this invention can be combined with each other.
[0050] Unless otherwise stated, percentages and parts are weight percentages and weight parts.
[0051] Experimental methods not specified in the instructions and examples are generally performed under standard conditions or as recommended by the manufacturer.
[0052] The various raw materials, reagents and components used in this invention are all commonly used raw materials in the field unless otherwise stated.
[0053] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as are familiar to those skilled in the art. Furthermore, any methods and materials similar to or equivalent to those described herein may be used in the methods of this invention.
Claims
1. A dry-spread terrazzo flooring material, characterized in that: Includes the following raw material components by weight: 30-50 parts of cementitious material, 1-5 parts of composite admixture, 40-70 parts of dry-spreading inorganic-organic composite surface-activated modified gradient aggregate, 0.1-3 parts of water-reducing agent, and 0.1-2 parts of cellulose ether; The cementitious material includes: A mixture composed of rapid-hardening sulfoaluminate cement and ordinary silicate cement in a mass ratio of 1-3:7-9; The composite admixture includes: A mixture composed of citric acid retarder, lithium carbonate early strength agent, and organosilicon defoamer in a mass ratio of 0.1–1:0.1–2:0.1–0.5; The dry-spreading-specific inorganic-organic composite surface-activated modified gradient aggregate includes: Coarse aggregate, medium aggregate, fine aggregate and micro filler are subjected to surface double modification treatment and graded in a mass ratio of 2-4:1-3:1-2:0.5-1. The surface dual modification treatment is as follows: first, the aggregate is hydrophobically modified with vinyltriethoxysilane, and then grafted with polycarboxylate superplasticizer, so that the aggregate surface has both chemical reactivity and dispersibility with cement hydration products. The dry-spread terrazzo flooring material is applied and used in the following ways: After the concrete base layer is pre-activated at the interface, the dry-spread terrazzo flooring material is spread in two stages, first vertically and then horizontally, and then compacted using a vibratory roller.
2. The dry-spread terrazzo flooring material according to claim 1, characterized in that: The coarse aggregate is sintered ceramic particles or dyed basalt with a particle size of 2-4 mm. The medium aggregate is natural quartz sand with a particle size of 0.5 to 1.5 mm; The fine aggregate is nano-alumina modified glass microspheres with a particle size of 0.1-0.3 mm; The microfiller is a mixture of activated metakaolin with a particle size of 20-100 nm and nano-calcium carbonate in a mass ratio of 1-2:0.5-1.
3. A method for preparing the dry-spread terrazzo flooring material according to claim 1, characterized in that: According to the formula, the gelling material, composite additive, water-reducing agent and cellulose ether are added to the dry powder mixing equipment and mixed evenly. Then, the dry-spreading special inorganic-organic composite surface-activated modified gradient aggregate is added, and the stirring speed is increased to continue mixing for 10 to 20 minutes to ensure that all components are fully dispersed and mixed evenly to obtain the dry-spreading terrazzo flooring material.
4. A construction method for the dry-spread terrazzo flooring material as described in claim 1, characterized in that: Includes the following steps: S1. Concrete base pretreatment: Pour concrete base and level it; S2. Interface pre-activation: Spray nano-silica sol interface agent onto the leveled concrete base surface; S3. First application: When the concrete surface reaches the predetermined state, the dry-spread terrazzo flooring material is evenly spread perpendicular to the concrete pouring direction; S4. First compaction: Use a vibratory roller to compact the surface of the spread dry-spread terrazzo flooring material; S5. Second application: Evenly spread the dry-spread terrazzo flooring material parallel to the concrete pouring direction; S6. Second compaction: Use a vibratory roller to compact the surface of the dry-spread terrazzo flooring material and smooth the edges and corners; S7. Maintenance and Polishing: After the construction is completed, moisturize and maintain the surface, then polish and grind. in, The dry-spread terrazzo flooring material used in the first spreading step S3 and the second spreading step S5 is the same material with the same proportion; or, The dry-spread terrazzo flooring materials used in the first spreading step S3 and the second spreading step S5 are two different materials with different proportions, and the weight ratio of coarse aggregate in the material used in the first spreading step is higher than that in the material used in the second spreading step.
5. The construction method of the dry-spread terrazzo flooring material according to claim 4, characterized in that: In step S2, the spraying dosage of the nano-silica sol interface agent is 0.1-0.2 kg / m².
6. The construction method of the dry-spread terrazzo flooring material according to claim 4, characterized in that: In step S3, the predetermined state is when the water seepage on the concrete surface disappears and the depth of finger pressing is 3-5 mm.
7. The construction method of the dry-spread terrazzo flooring material according to claim 4, characterized in that: In step S3, the amount of dry-spread terrazzo flooring material used in the first application is 6-8 kg / m². And / or, In step S5, the amount of dry-spread terrazzo flooring material used in the second spreading is 4-6 kg / m².
8. The construction method of the dry-spread terrazzo flooring material according to claim 4, characterized in that: The compaction described in step S4 causes the coarse aggregate in the dry-spread terrazzo flooring material to embed into the concrete base layer to a depth of 2-3 mm.
9. The construction method of the dry-spread terrazzo flooring material according to claim 4, characterized in that: The floor structure formed by the construction method is a gradient structure integrated with the concrete base layer, comprising, from bottom to top: The surface consists of a penetrating bonding layer formed by the reaction of nano-silica sol with hydration products on the concrete surface; an aggregate embedding layer formed mainly by the mechanical interlocking and chemical bonding of coarse aggregate in the dry-spread terrazzo flooring material with cement hydration products; and a dense surface layer formed mainly by the compaction of medium aggregate, fine aggregate and micro filler in the dry-spread terrazzo flooring material.
10. The construction method of the dry-spread terrazzo flooring material according to claim 9, characterized in that: The thickness of the permeation bonding layer is 1-2 mm; The thickness of the aggregate embedding layer is 3-4 mm; The thickness of the dense surface layer is 1 to 2 mm.